Serbs in the Požega basin - Škiljan, Filip (Historical Thought, 2025)
In the text, the author provides an overview of the history of the Serbs in the Požega valley using archival material, literature and interviews with the remaining members of the Serbian national minority. The author first brings information about the circumstances of Serb immigration to the area of the Požega valley, and then deals with the customs and way of life of the Serbs. He devoted a special chapter to the Second World War. The socialist period was covered in the following chapter, which also covered the culture of remembrance of the Second World War and the neglect of religion. The last chapter deals with the Homeland War in the Požega valley and the suffering of Serbs in that area.